The development and preliminary validation of a social-emotional skills assessment instrument for lower secondary school students - Einpaul, Piret; Leijen, Äli; Baucal, Aleksandar (Psihološka istraživanja, 2024)
Given the necessity of comprehensive and psychometrically sound instruments to measure students’ social-emotional skills (SEMS) in school context and facet level, this study aimed to develop and evaluate a SEMS assessment instrument for lower secondary school students.  The initial version of the instrument was developed based on the descriptions of skills from SEMS frameworks by Primi et al. and OECD and consisted of 48 items. After confirmatory factor analysis (CFA) with a sample of 204 students from Estonia, a 9-factor and 34-item instrument was refined. This model was confirmed with acceptable fitness by CFA with another sample of 521 students. Strict measurement invariance was established between grade groups (grades 6 and 9). In conclusion, while analyses show promise and the instrument allows assessing students’ SEMS in lower-secondary schools, further research is required.
Keywords: social-emotional skills, student evaluation, instrument development, confirmatory factor analysis, measurement invariance